1973
DOI: 10.1136/bmj.4.5892.571
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunotherapy Used Alone for Maintenance of Patients with Acute Myeloid Leukaemia

Abstract: SummaryA total of 32 patients suffering from acute myeloid leukaemia were initially treated with daunorubicin and cytosine arabinoside, and eight who achieved full remission were given a brief cytoreduction course of cyclophosphamide and thioguanine. Of these eight patients seven were then actively immunized with 10' irradiated allogeneic acute myeloid leukaemia cells and B.C.G. at weekly intervals. Six of these patients have survived in apparent good health for more than one year. Bone marrow changes suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1

Year Published

1975
1975
1978
1978

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 7 publications
1
18
1
Order By: Relevance
“…We found that second remissions were the rule (6/7 patients), while third and subsequent remissions commonly occurred (Freeman et al, 1973), in contrast to the general experience that relativelv few patients achieved second remission in adult AML (Wiernik and Serpick, 1970;Bailey et al, 1971;Crowther et al, 1973;Powles, 1973;Powles et al, 1973Powles et al, , 1977. There are few reports of third remissions (Whittaker and Slater, 1977 examination was repeated within 2 weeks.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…We found that second remissions were the rule (6/7 patients), while third and subsequent remissions commonly occurred (Freeman et al, 1973), in contrast to the general experience that relativelv few patients achieved second remission in adult AML (Wiernik and Serpick, 1970;Bailey et al, 1971;Crowther et al, 1973;Powles, 1973;Powles et al, 1973Powles et al, , 1977. There are few reports of third remissions (Whittaker and Slater, 1977 examination was repeated within 2 weeks.…”
contrasting
confidence: 57%
“…A blast count > 8 0 was taken as definite indication of relapse, even in the absence of clinical and peripheral blood changes. Immunotherapy with irradiated allogeneic AML blast cells and BCG (Glaxo) was administered at weekly intervals as described previously (Freeman et al, 1973).…”
mentioning
confidence: 99%
“…WE ARE treating a number of acute myeloid leukaemia (AML) patients during remission with active immunotherapy (see Freeman et al, 1973) and without maintenance chemotherapy. The treatment protocol is based on immunotherapy trials carried out at the Royal Marsden and St Bartholomew's Hospitals (Powles et al, 1973) and entails the weekly injection of x-irradiated allogeneic (donor) AML blasts subcutaneously into 3 of the patient's limbs and BCG into the fourth.…”
mentioning
confidence: 99%
“…A group in Manchester (Freeman et al, 1973) followed the same immunotherapy protocol as used here, and, whilst they did not carry controls in their clinical trial, they commented on the ease with which patients who had received immunotherapy without maintenance chemotherapy achieved a second remission, and also noted the long period of survival after relapse in this group.…”
Section: Mechani8ms Of Prolongation Of Life By Immunotherapymentioning
confidence: 99%